Análise dos meios e métodos de preparação física e monitoramento das cargas utilizados por treinadores brasileiros de nado artístico da categoria sênior - Nóbrega, Helena Longo Fernandes (2022)
INTRODUCTION: Artistic Swimming (AN) requires hight-level physical preparation (PP) and little is known about the means, training methods and monitoring of loads applied during FP routines of an athlete of this modality. OBJECTIVE: To analyze the PP and the process of monitoring training loads used by Brazilian AS athletes’ coaches in the senior category. METHODS: 14 coaches, with 10.5 ±5.3 years of experience in the sport, of which 64.3% train athletes who compete at international level, answered a questionnaires (Google Forms), previously submitted to content validation (IVCt 0.96) done by 7 experts. The questions were regarding the means and methods of training and load monitoring used. The coorelations range in magnitude were analyzed concerning the coaches’ years of practice experience and their choices of training programs, as well as the act of monitoring training loads. Microsoft Excel 2016 and SPSS – 21.0 were used to analyze the data, with a statistical significance of P ≤ 0.05. RESULTS: For 28.6% of the participants, the main function of PP programs is to increase flexibility; for 21.4% it is transference, increase in athletic performance and resistance; and for 12.3% it is increase in strength and decrease in injuries frequency. Concerning the physical abilities prioritized in PP, 100% of the trainers listed flexibility and aerobic power. 92.6% also considered the practical implementation of anaerobic power and strength training. The most used training methods to develop specific physical capacities were the practice of static stretching to obtain improvements in flexibility (78.6%); specific choreographic training for the variables related to aerobic power (51.1%); traditional training (with free weights and gym equipament) to obtain strength (42.9%); plyometrics; Olympic weightlifting and specific training with elastic bands to obtain muscular power (21.4%); and, finally, specific choreographic training (64.3%) for anaerobic power. All participants perform some kind of physical training out of the water to improve specific PP. 100% of the specific coaches stated they use Zala training, 78.6% use load monitoring tool to make adjustaments to the prescription with distinctions in the frequency of adjustments. The two main strategies used to monitor the training loads are the Rate of Perceived Exertion (35.7%) and Neuromuscular Tests. A moderate negative correlation between the years of practice experience factor and training loads monitoring was verified (r = 0,71). CONCLUSION: there is a preference for methods inside and outside the water environment, although the aerobic and anaerobic power trainings prioritize inside the water practices; there is a wide adherence to Zala methodology; homogeneity was not observed in the PP implementation in relation to the frequency and destined hours; the inconsistency of the national calendar is pointed out as a limiting element of the preparation process; the load monitoring is performed with a variety of strategies and load adjustment times.